The ER Is a Common Mediator for the Behavior and Interactions of Other Organelles - Mathur, Jaideep; Kroeker, Olivia Friesen; Lobbezoo, Mariann; Mathur, Neeta (Frontiers in Plant Science, 2022)
Optimal functioning of a plant cell depends upon the efficient exchange of genetic information, ions, proteins and metabolites between the different organelles. Intuitively, increased proximity between organelles would be expected to play an important role in facilitating exchanges between them. However, it remains to be seen whether under normal, relatively non-stressed conditions organelles maintain close proximity at all. Moreover, does interactivity involve direct and frequent physical contact between the different organelles? Further, many organelles transition between spherical and tubular forms or sporadically produce thin tubular extensions, but it remains unclear whether changes in organelle morphology play a role in increasing their interactivity. Here, using targeted multicolored fluorescent fusion proteins, we report observations on the spatiotemporal relationship between plastids, mitochondria, peroxisomes and the endoplasmic reticulum in living plant cells. Under normal conditions of growth, we observe that the smaller organelles do not establish direct, physical contacts with each other but, irrespective of their individual form they all maintain intimate connectivity with the ER. Proximity between organelles does increase in response to stress through concomitant alterations in ER dynamics. Significantly, even under increased proximity the ER still remains sandwiched between the different organelles. Our observations provide strong live-imaging-based evidence for the ER acting as a common mediator in interactions between other organelles.